2015
DOI: 10.1089/end.2015.0118
|View full text |Cite
|
Sign up to set email alerts
|

Palpable Undescended Testes: 15 Years of Experience and Outcome in Laparoscopic Orchiopexy

Abstract: Laparoscopy is a great and safe option for patients with palpable undescended testes, regardless of its position in the inguinal canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…10 Riquelme et al treated 192 cryptorchid palpable testes with laparoscopy and found the excellent outcomes -only 2 (0.4%) testicles had reascended, and there was no testicular atrophy. 8 Similarly, Elderwy et al revealed that laparoscopic orchiopexy had a comparable success rate with open orchiopexy, and laparoscopy was relatively more effective, as it had less redo cases. 3 A study from He et al reported 103 inguinal canalicular palpable undescended testes that were managed with laparoscopy.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…10 Riquelme et al treated 192 cryptorchid palpable testes with laparoscopy and found the excellent outcomes -only 2 (0.4%) testicles had reascended, and there was no testicular atrophy. 8 Similarly, Elderwy et al revealed that laparoscopic orchiopexy had a comparable success rate with open orchiopexy, and laparoscopy was relatively more effective, as it had less redo cases. 3 A study from He et al reported 103 inguinal canalicular palpable undescended testes that were managed with laparoscopy.…”
Section: Discussionmentioning
confidence: 98%
“…First, laparoscopy could provide a wide range of testicular dissection and complete releasing of spermatic vessels, which allow for satisfactory orchiopexy. 6,8 By this way, it can improve the length of spermatic cord and bring down the testis to the button of scrotum without tension. Conversely, in open surgery the dissection is difficult in the retroperitoneum close to the lower pole of the kidney.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, Riquelme et al indicated that LO was a safe procedure for patients with palpable undescended testes, and no more complications were found compared to the traditional surgery. Of 192 patients studied, only one case was converted to TIO [7,10]. However, based on the surgeon's preference and experience, inguinal and prescrotal techniques are still recommended for palpable UDT undergoing surgery [11].…”
Section: Discussionmentioning
confidence: 99%